Preparation and characterization of tree-like cellulose nanofiber membranes via the electrospinning method. (1st March 2018) - Zhang, Kai; Li, Zongjie; Kang, Weimin; Deng, Nanping; Yan, Jing; Ju, Jingge; Liu, Yong; Cheng, Bowen
Highlights: Tree-like cellulose nanofiber membranes are prepared via electrospinning and deacetylation treatment. The membranes had excellent hydrophilicity, small average pore size, preferable mechanical properties and strong resistance to organic solvent. Abstract: A novel tree-like cellulose nanofiber membrane was controllably fabricated via the electrospinning method by adding certain amount of tetra butyl ammonium chloride (TBAC) into the cellulose acetate solution followed by a deacetylation treatment process. The morphological structure, material structure and air filtration performance of both the cellulose and the cellulose acetate tree-like nanofiber membranes were characterized. Water contact angles, mechanical properties, and air filtration properties were also evaluated. The air filtration efficiency of cellulose acetate tree-like nanofiber membrane can reached 99.58%, and the eventually cellulose tree-like membrane still maintain 98.37%. The eventual cellulose tree-like nanofiber membranes exhibited small pore size, excellent hydrophilicity, good solvent resistance and preferable mechanical property. The small average pore size caused by the tree-like structure and the strong resistance to organic solvent can make it a potential candidate for the membrane separation.